Disability-related disparities in health outcomes among newly diagnosed diabetic patients: A retrospective cohort - Sujin Kim; Boyoung Jeon (BMC, 2024)
Abstract Background A distinct gap in the literature persists regarding the health outcome of individuals with Type 2 diabetes who also have disabilities. This study aimed to investigate potential disparities in events occurrence among diabetes patients across various disability stages. Methods We conducted a retrospective cohort study on patients newly diagnosed with diabetes in 2013 and 2014, aged ≥ 18 years, and followed them until December 2021, using data from the Korean National Health Insurance database. All-cause mortality and hospitalization for diabetes mellitus and cardio-cerebrovascular diseases (CVD) was assessed. Results The study included 26,085 patients, encompassing individuals without disabilities and those with physical, visual, hearing and speech, intellectual and developmental, and mental disabilities. After adjustment, individuals with disabilities had a higher risk of all-cause death (adjusted hazard ratio [aHR]: 1.25, 95% CI: 1.07-1.48) compared to those without disabilities. In particular, severe disabilities and hearing and speech disabilities showed significantly higher risks of all-cause death (aHR: 1.40, 95% CI: 1.06-1.85 and aHR: 1.58, 95% CI: 1.17-2.15, respectively), with marginal significance for mild disabilities (aHR: 1.20, 95% CI: 0.99-1.45) and mental disorders (aHR: 1.92, 95% CI: 0.98-3.73). Patients with disabilities also had significantly increased risks of CVD-related first admissions (aHR: 1.30, 95% CI: 1.07-1.56) and diabetes-related first admissions (aHR: 1.31, 95% CI: 1.20-1.43) compared to those without disabilities. Conclusions This study underscores the urgent need for public health policies to prioritize individuals with disabilities and diabetes, addressing the disparities in health outcome.